The detection rate and influencing factors of high-risk groups of cardiovascular disease in Anhui, China: A cross-sectional study of 99,821 residents - Xing, Xiu-Ya; Wang, Zhi-Xin; Cao, Ya-Wen; Wang, Xin-Yi; Zhang, Luan; Chen, Ye-Ji; Wang, Hua-Dong; Xu, Jing-Qiao; Niu, Mi-Xue; Liu, Zhi-Rong; Tao, Sha-Sha (Frontiers in Public Health, 2022)
Objective To investigate the detection rate and influencing factors of high-risk population of cardiovascular disease in Anhui province. Methods From March 2017 to August 2019, the residents aged 35-75 years old were selected using the multi-stage stratified cluster sampling method in 8 counties and districts of Anhui Province, and questionnaire survey, anthropometric measurement, and collection of biological samples were carried out among them. Results A total of 99,821 residents in Anhui Province were finally investigated, and among them 21,426 residents were detected to be high-risk groups of cardiovascular disease. The detection rate of high-risk groups was 21.46%. According to the high-risk types, the high-risk groups can be clustered. 74.57% of them had only one high-risk type, 22.57% of them had two high-risk types, and 2.86% had three or more high-risk types. The results of Generalized Linear Mixed Model (GLMM) showed that male, age ≥ 45 years old, not married, occupation as a farmer, annual family income < 25,000 yuan, drinking, overweight and obesity, pre-central obesity and central obesity, snoring, feeling fatigued, sleepiness, and self-reported history of diabetes were more likely to be risk factors of cardiovascular disease (all P value <0.05). Conclusion The detection rate of high-risk groups of cardiovascular disease in Anhui Province is relatively high. Individualized intervention measures as well as comprehensive prevention and control strategies should be adopted focusing on the distribution characteristics of risk factors of high-risk groups.